Ta doping for an enhanced efficiency of TiO2 nanotube based dye-sensitized solar cells - Lee, Kiyoung; Schmuki, Patrik (Electrochemistry Communications, 2012)
Ta doped TiO2 nanotube layers were fabricated by anodization of different Ti–Ta alloys with Ta contents of 0.03, 0.1 and 0.4 at.%. For all layers well defined nanotubular structures could be formed. The layers were then characterized in dye-sensitized solar cells. Under optimized conditions, that is for a 0.1 at.% Ta alloy, the solar cell efficiency could be enhanced by 25% compared to non-doped TiO2 nanotubes. Intensity modulated photocurrent spectra (IMPS) and intensity modulated photovoltage spectra (IMVS) measurements performed with the solar cells indicate that the beneficial effect is due to suppression of recombination effects.
EAM Import::2019-03-12